O envelhecimento dos migrantes: diálogos com maranhenses residentes em São Paulo - Carvalho, Livia Cristina Costa (2007)
This study discusses the meaning of aging to migrants through the life experience of the the maranhenses in the city of Sao Paulo. One calls migrant the individual who moves from one place to another within a particular country. Becoming old in the city of São Paulo, a metropolis, whether bringing or not their family nucleus along with them, causes important repercussions that affect the migrants subjective aspects and social relations. Therefore, the qualitative approach was chosen as the method to identify the specifics of the aging process of such migrants, without separating the individuals from their historical background. By making use of the existing social networks, the researcher tried to find people interested in participating in this essay. A total of four people were interviewed, three men and a woman, between the ages of sixty-two and seventy. They have all been living in São Paulo for more than two decades. Their memories helped them recover the journey they endured throughout the time, and as they told their life experiences, new meanings were formed. At the end, we can affirm that there is not a pattern for the old maranhense migrants. If they have been able to accomplish the goal that caused them to migrate, the feeling of nostalgia is not expressed excessively idealized. However, both for those who affirm to feel satisfied at the metropolis as for those who dream of going back to their home towns, their cultural backgrounds are a strong element of comfort as they face aging